On Migration, Identity, And Literature In French Language Teaching - Pecníková, Jana (E- Revista de Estudos Interculturais, 2021)
Developing of current cultural and social issues in education is the main goal of the Erasmus + project called Development of a Collaborative Space for French as a Foreign Language: Literature, Migration, Exile and Learning project (DECLAME´FLE). Based on a common international platform consisting of three universities (Université de Rennes 2, Matej Bel University in Banska Bystrica, Adam Mickiewicz University in Poznan), we work to integrate social topics such as migration and exile into teaching French as a foreign language. It is processed through literary texts, into the training of future teachers and translators of French, to increase their linguistic and intercultural competence. The basis of work with students is primarily a literary, linguistic, and intercultural analysis of the corpus of selected literary works by French-speaking authors of non-French-speaking origin, who develop the theme of migration and exile in their works. In this paper, we focus on the socio-cultural level of the connection between literature, migration, and identity, from the perspective of the main character Martin in the selected literary work of Andrea Salajova - Eastern.